Branched Tröger's base polymer membranes for gas separation. (2nd December 2022) - Yue, Junbo; Hou, Jingjing; Li, Yixuan; Yang, Yanqin; Han, Lu; Sun, Shuzheng; Li, Jingde
Abstract: Here we report the synthesis of branched Tröger's base polymers ( x -BTB) with different degree of tetraphenylmethane branch structure by incorporating varied amounts of tetrakis(4-aminopheny)methane into the main chains of Tröger's base polymer (TB). We show that branching increases porosity of x -BTB, leading to improved gas permeability. Specifically, the BET surface area and pore volume of x -BTB polymers increase continuously from 410 to 544 m 2  g −1 and 0.584–0.607 cm 3  g −1, respectively, for branched polymers containing progressively more branch structure. For CO2 /N2, CO2 /CH4, and O2 /N2 binary gas separation, a significant improvement in the gas permeability without obvious compromising the membrane selectivity is observed on the x -BTB membranes with higher branch degree. In particular, for CO2 /N2 binary gas separation, the CO2 permeability of 5 wt%-BTB membrane is 145 Barrers, creating an enhancement of 64.8% as compared to TB membrane. Moreover, x -BTB membranes are much more resistant to physical aging than TB membrane. These results suggest that introduction of tetraphenylmethane branch structure is an effective strategy to fabricate polymeric membranes with high performance suitable for gas separation applications. Graphical abstract: Image 1 Highlights: Tetrakis(4-aminopheny)methane (TAPM) exhibited a rigid tetrahedral structure. Incorporating TAPM into the backbones of TB yielded branched TB polymer ( x -BTB). x -BTB polymers exhibited higher BET surface area than that of TB polymer. The obtained x -BTB membranes showed a significantly improved gas permeability.